Improving the quality of assessment by using a community of practice to explore the optimal construction of assessment rubrics. Issue 3 (4th May 2017) - Grainger, Peter; Christie, Michael; Thomas, Glyn; Dole, Shelley; Heck, Deborah; Marshman, Margaret; Carey, Michael
Abstract: A focus on quality assurance of assessment processes in tertiary education within Australia and throughout the world has resulted in a changing landscape of assessment types and grading schemes over the last decade. The use of criteria and standards-based assessment systems are now very commonplace in tertiary education. There are a variety of models now used, but typically they include a criteria sheet and a levelled rubric. An alternative to the traditional matrix-style rubric is the Continua Model of a Guide to Making Judgments (GTMJ). In this paper, we analyse available assessment models and their capacity to guide the marking, grading and moderation of student assessment tasks. We specifically address standards descriptors used to identify the quality expected at each standard. The research was undertaken through a community of practice within the School of Education at a tertiary institution where the collective goal of enhancing assessment grading tools to improve student outcomes was approached through a process of peer review. In our results section, we analyse the efficacy of an internal peer-review model as part of a community of practice and the professional learning about grading tools that occurs.